Perception of nurses about palliative care: Experience from a private hospital in west Indonesia - Yenni Ferawati Sitanggang; Feni Vitriani Laoli; Fritania Lawolo; Gloria Narwasti Kiha; Gracia Manihuruk (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: Palliative care is a method for patients and their families facing life-threatening conditions to improve their quality of life. Nurses have a critical role on the palliative care team, and as such, they must have an accurate perception of palliative care.Purpose: To identify nurses’ perceptions about palliative care: from a private hospital in west IndonesiaMethod: This research is a descriptive research conducted with a cross sectional design. Participants were recruited using a purposive sampling technique from a private hospital in West Indonesia, with a population of 238 nurses from all wards. All nurses who had worked for at least two years and agreed to participate in the study were included. Slovin's algorithm was used to determine the sample size, which resulted in 149 nurses. However, only 105 nurses answered the questionnaire and completed it.Results: The results indicated that the majority of nurses were female in their early twenties. The study demonstrated that nurses had an exceptional grasp of the definition and philosophy of palliative care, albeit certain concerns remained unanswered.Conclusion: In conclusion, providing palliative care training will improve nurses’ knowledge as well as their practice in palliative care.